A Multi-level Evidence-based Cyber Crime Prosecution Information System - Adah Agana, Moses; Wario, Ruth (International Journal of Engineering and Technology, 2018)
This research work was designed to utilize multi-level cyber crime detection and control system to provide enhanced real-time evidence to cyber crime investigators to aid them in prosecuting cyber criminals. The design was based on a robust system combining user-identity, device identity, geographical location and user activities to provide evidences to uniquely identify a cyber user and detect crimes committed. The system captures the userâ€™s facial image and biometric finger print as mandatory login parameters in addition to username and password before granting access. The system was tested and implemented in a real time cyber security website www.ganamos.org.Â The results showed that it is possible to divulge the identity of cyber users and associate their activities with the devices they use, the date, time and location of operation. These can provide real-time evidences to law enforcement agencies to track down and prosecute cyber criminals.Â